Liver transplant program. Critical population mass and community need - Ruso, Luis; Risi, Leonardo; Balboa, Oscar (Cirugía del Uruguay, 1996)
Despite its proved efficacy hepatic transplant (HT) involves a therapy of high complexity and raised cost. In Uruguay, with its /ow number of inhabitants, the need far HT has been challenged. The aim of this report is to justify the need of an HT program with an analysis of the population critica! mass, medica/ care requirements and thevarious factors affecting the patient and its social setting at pre and post transplant. A/so dealt with are the contributions of an HT program to global improvement of care, particular/y hepatopathies. lt is concluded that an HT, in Uruguay, is ful/y justified in conjunction with current demand and with the fact that its population mass warrants prediction of a higher number of 15 HT's per mil/ion inhabitants.